2021
DOI: 10.21037/apm-20-1116
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced lung damage in patients treated with stereotactic body radiotherapy after EGFR-TKIs: is there any difference from stereotactic body radiotherapy alone?

Abstract: Background: To quantitatively evaluate lung damage after treatment of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and stereotactic body radiotherapy (SBRT) in patients with nonsmall cell lung cancer (NSCLC), and compare that of SBRT only treatment.Methods: Eligible patients from an IRB-approved prospective clinical trial had one month of EGFR-TKIs treatment followed by SBRT (TKI + SBRT) and with 3-month follow-up high resolution CT. NSCLC patients treated with SBRT alone during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Given that previous studies have reported that epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) combined with radiotherapy were more inclined to develop RILI ( 33 , 34 ), we further explored the correlation between the 5 core target genes and EGFR using the TIMER 2.0 database. We found that the expression of EGFR was closely associated with AKT1, NOTCH1, SIRT1 and PTEN ( P <0.05), but not TP53 ( P >0.05) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that previous studies have reported that epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) combined with radiotherapy were more inclined to develop RILI ( 33 , 34 ), we further explored the correlation between the 5 core target genes and EGFR using the TIMER 2.0 database. We found that the expression of EGFR was closely associated with AKT1, NOTCH1, SIRT1 and PTEN ( P <0.05), but not TP53 ( P >0.05) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of a prospective, single-arm, Phase II study suggest that the early SBRT of a primary lesion after EGFR-TKI therapy is a potentially safe and effective new approach for treating EGFR-mutant advanced NSCLC [45]. However, Tang et al [46] found that, compared with patients treated with SBRT alone, patients treated with EGFR-TKIs combined with SBRT were more likely to develop radiation pneumonitis. The safety and efficacy of SBRT combined with targeted therapy must be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Of these examples, lung injury may be a potentially fatal event. A recent prospective clinical trial ( 59 ) showed that patients treated with EGFR-TKIs + stereotactic body radiation therapy (SBRT) were more likely to develop radiation pneumonitis (25% vs. 0%) when compared with the SBRT alone treatment group, with 4/20 patients developing grade 2 and above pneumonia. However, due to the small number of patients and no observed statistical differences, it was difficult to conclude that EGFR-TKIs combined with Radiation Therapy (RT) increased the risk of radiation-induced lung injury.…”
Section: Lat Safety In Oligometastatic Nsclcmentioning
confidence: 99%